2018
DOI: 10.1007/s13346-018-0584-7
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming transporter-mediated multidrug resistance in cancer: failures and achievements of the last decades

Abstract: Multidrug resistance (MDR) is a complex phenomenon caused by numerous reasons in cancer chemotherapy. It is related to the abnormal tumor metabolism, precisely increased glycolysis and lactic acid production, extracellular acidification, and drug efflux caused by transport proteins. There are few strategies to increase drug delivery into cancer cells. One of them is the inhibition of carbonic anhydrases or certain proton transporters that increase extracellular acidity by proton extrusion from the cells. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 146 publications
1
23
0
Order By: Relevance
“…The source of the miRNA candidate influences how accessible it is as a biomarker, how the miRNA is extracted from the biological specimen, and even how it is analyzed. In fluid specimens such as blood, the miRNA content can originate through a few pathways, including extracellular vesicles (exosomes) (Kanlikilicer et al., 2016; Bayraktar et al., 2017; Rashed et al., 2017; Paskeviciute and Petrikaite, 2019). Ongoing investigations continue to probe whether enrichment of exosomes from biological samples or more crude cell-free preparations are more reliable in biomarker measurements; and some reports suggest it may depend on the specific human disease.…”
Section: Mirnas As Biomarkers In Clinical Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The source of the miRNA candidate influences how accessible it is as a biomarker, how the miRNA is extracted from the biological specimen, and even how it is analyzed. In fluid specimens such as blood, the miRNA content can originate through a few pathways, including extracellular vesicles (exosomes) (Kanlikilicer et al., 2016; Bayraktar et al., 2017; Rashed et al., 2017; Paskeviciute and Petrikaite, 2019). Ongoing investigations continue to probe whether enrichment of exosomes from biological samples or more crude cell-free preparations are more reliable in biomarker measurements; and some reports suggest it may depend on the specific human disease.…”
Section: Mirnas As Biomarkers In Clinical Medicinementioning
confidence: 99%
“…Accumulating evidence, however, shows that the ATP-binding cassette (ABC) transporter family of proteins that activate drug resistance are regulated by miRNAs (Guo et al., 2018; Xie et al., 2018). The ABC family includes P-glycoprotein (Pgp), multidrug resistance-associated proteins (MRP), and breast cancer resistance proteins (BCRP), all of which can pump out drugs to create additional biological energy through ATP hydrolysis (Choi, 2005; Paskeviciute and Petrikaite, 2019). A recent report suggests miR-298 binds to the Pgp gene, thereby silencing the expression of Pgp and its ability to pump out antiepileptic drugs (Xie et al., 2018).…”
Section: Drug Resistance and Mirnasmentioning
confidence: 99%
“…22,23,27 Moreover, mounting evidences show that drug resistance including MDR is closely correlated with the abnormal expression of transport proteins, anomalous tumor metabolism, and increased glycolysis and lactic acid production in cancers including leukemias. 28,29 For example, the inhibition of glycolysis reduced the activity of Akt/mammalian target of rapamycin (mTOR)/hypoxia-inducible factor-1a (HIF-1a) axis and improved tamoxifen sensitivity in antiestrogen-resistant breast cancer cells. 30 The suppression of glycolysis by 2-DG, lonidamine (LND), or 3-bromopyruvate (3-BrPA) enhanced the 31 Previous studies showed that ADR resistance was closely related with glycolysis responses in AML and CML.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer MDR manifests cross resistance to several structurally and mechanically different chemo-agents and could be contributed to the following reasons [2]. The change in tumor microenvironment [3][4][5], decreased drug uptake [6], adapted cell apoptotic pathways [7][8][9], drug inactivation through metabolism [10,11], the influence of epigenetic regulation [12,13], mutation of drug target site [14], and the increased drug efflux [15] have been reported to play important roles in causing cancer MDR. Among the above mechanisms, the increased drug efflux by ATP-binding cassette (ABC) transporters has been regarded as the most influential cause.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the P-gp inhibitory and MDR modulating information of the caffeic acid was insufficient and warrants further detailed investigation. inactivation through metabolism [10,11], the influence of epigenetic regulation [12,13], mutation of drug target site [14], and the increased drug efflux [15] have been reported to play important roles in causing cancer MDR. Among the above mechanisms, the increased drug efflux by ATP-binding cassette (ABC) transporters has been regarded as the most influential cause.…”
Section: Introductionmentioning
confidence: 99%